How do reminder systems in follow-up screening for women with previous gestational diabetes work? - a realist review - Jane Hyldgaard Nielsen; G. J. Melendez-Torres; Torill Alise Rotevatn; Kimberly Peven; Kirsten Fonager; Charlotte Overgaard (BMC, 2021)
Abstract Background Women with previous gestational diabetes have an increased risk of developing type 2 diabetes later in life. Recommendations therefore urge these women to participate in follow-up screening, 4-12 weeks postpartum and every 1-3 years thereafter. We sought to theorize how reminder interventions to support early detection of diabetes work, for whom, and in what circumstances. Methods We used a method informed by realist review and synthesis. A systematic, iterative search in six electronic databases (PubMed, MEDLINE Ovid, The Cochrane Library, CINAHL, EMBASE) had a primary focus on experimental intervention studies and included additional information in relation to identified intervention studies. Analysis inductively identified context-mechanism-outcome configurations present in the evidence. Results We located 16 articles eligible for inclusion. A cross-case comparison identified seven grouped context-mechanism-outcome configurations leading to intervention mechanisms relating to changes in women's reasoning and behavior. Configurations were thematically ordered in relation to Systems Resources, Women's Circumstances, and Continuity of Care. These were mapped onto a socio-ecological model and discussed according to identified middle-range theories. Conclusion Our findings adds to the body of evidence, that reminders have the potential to be effective in increasing participation in the recommended follow-up screening. Our study may assist researchers and policy and decision makers to analyze and judge if reminders are feasible and/or likely to succeed in their specific context. Further research into the perspective of socially disadvantaged and overweight women is needed to avoid unintended consequences such as social inequality in service use and stigmatization in future programs.